Violence, restorative justice and forgiveness: dyadic forgiveness and energy shifts in restorative justice dialogue - Armour, Marilyn Peterson (Jessica Kingsley Publishers, 2018)
Dyadic forgiveness in restorative justice : a review of the field and a proposed model -- Victim offender mediation dialogue evaluation : a growth curve modeling approach -- Victim case narratives and analysis -- Mapping dyadic forgiveness : an analysis of positive energy shifts in restorative justice dialogue